The literary text in turbulent times: an instrument of social cohesion or an eruption of ‘critical’ bliss. Notes on J M Coetzee’s Life and times of Michael K - Van Niekerk, Marlene (University of the Free State, 2013)
The article is developed as a “counter-cultural” response to the socio-utilitarian formulations around artistic production typically found in current mission statements of the EU Culture Program. In its argument against the instrumentalisation of art, the article builds on the hypothesis that the ethical import of art lies not in the “messages” (e.g. about the need for European social cohesion and “cosmopolitan feelings”) that could be extracted from it, but in its own formally coherent and conceptual complexity. With reference to perspectives on art developed by Jean-Luc Nancy, Roland Barthes and Deleuze and Guattari, a reading is offered of J.M. Coetzee’s fourth novel Life and Times of Michael K. that suggests how it could be used as an oppositional intervention through analysis of its outrageously subversive conceptual charge, its abject main character and its self-conscious deconstructivist anti-realist style.
Keywords: EU Culture Program; Coetzee, J. M.; Life and times of Michael K